Global problems in sexual offenses - Erbaş, Rahime (Lexington Books, 2022)
Challenges in regulating sexual offences in Turkey / by Rahime Erbaş -- Substantive and procedural challenges impeding an effective response to rape : the example of Greece / by Chara Chioni-Chotouman -- Sexual offences in the Republic of North Macedonia / by Nikola Tupancheski, Gordana Lazhetikj, Aleksandra Gruevska Drakulevski, and Aleksandra Deanoska Trendafilova -- A perspective on the evolution of the legal framework of sexual offences in Romania / by Cristian Dumitru Miheș & Carmen Adriana Domocoș -- Grooming re-examined : protection of children from sexual abuse in the Republic of Croatia / by Barbara Herceg Pakšić -- Combating sexual and gender-based violence in Serbia : Post- the Istanbul Convention / by Gordana Gasmi and Željko Nikač -- Sexual offences within close relationships : victims' vulnerability and criminal proceedings / by Lara Ferla -- Female genital mutilation as a gender-based violence / by Francesco Angelone and Angela Caruso.